CONSTRUCTING CULTURAL IDENTITY IN BIPA PEDAGOGY: A CRITICAL DISCOURSE ANALYSIS OF AR-ENHANCED LEARNING MATERIALS BASED ON CIREBON HERITAGE - Indrya Mulyaningsih; Tiwaporn Jan-Kaew; Tatik Ekawati; Veni Nurpadillah; Muhammad Arif Rahman (Universitas PGRI Sumatera Barat, 2026)
Integrating cultural identity into Bahasa Indonesia for Penutur Asing (BIPA) pedagogy often prioritizes content enrichment over discursive and ideological engagement. This study addresses this limitation by investigating how cultural identity is constructed, depicted, and facilitated through Augmented Reality (AR) within learning materials derived from Cirebon's historical landscape for Thai learners. Employing Critical Discourse Analysis (CDA) alongside design-based research, the study scrutinizes pedagogical designs, instructional texts, visual representations, and learner feedback to identify prevailing identity discourses embedded within the technology. Results indicate that Cirebon's cultural identity is predominantly portrayed through harmonious, heritage-focused narratives emphasizing tradition and historical continuity, whereas alternative or contested identities receive minimal representation. Consequently, AR functions not merely as a technological tool but also as a semiotic mechanism that validates specific cultural interpretations and pedagogical ideologies. The study argues that AR-enhanced BIPA materials function as ideological frameworks that significantly shape learners' perceptions of Indonesian cultural identity. This research advances BIPA instruction beyond technological augmentation, advocating for critical language education that acknowledges technology's role in perpetuating cultural ideologies. It highlights the need for educators to examine how digital media shapes learners' cultural understanding critically. Future research should conduct comparative discourse analyses across diverse cultural contexts and investigate learner resistance and reinterpretation of these narratives. By examining the intersection of technology, discourse, and identity, this study contributes to a nuanced understanding of digital pedagogy in language learning, ensuring that cultural representation remains critical rather than superficial.